Identifikasi Saluran Distribusi Dalam Rantai Pasokan Tomat Di Kecamatan Merdeka (Studi Di Desa Ujung Teran) - Franadita, Dwi; Lubis, Arbarija Hafiz; Aisyah, Siti (Universitas Labuhanbatu, 2022)
Supply chain is a system that involves the process of production, delivery, storage, distribution and sales process of products to meet the demand. Distribution channels are important in the supply chain, which is concerned with moving goods from one place to another effectively and efficiently. The purpose of this study was to identify the distribution channel of tomato supply chain in Ujung Teran Village, Merdeka District, Karo Regency. The analysis method used is qualitative. Data collection techniques by means of observation, interviews and documentation. The results showed that the process of potato distribution channels that occur in the village of Ujung Teran must pass through several hands include farmers, collectors, traders, just up to the hands of consumers. Farmers in Ujung Teran village should cut off existing distribution channels by selling the harvest directly to traders without going through collectors.